1986
DOI: 10.1161/01.atv.6.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for changes in aorto-iliac arterial compliance in healthy men.

Abstract: Doppier ultrasound was used to measure pulse wave velocity down the aorta and iliac arteries. Arterial wall compliance was calculated from pulse wave velocity in 45 apparently healthy men. Their arterial compliance fell significantly with advancing age, raised blood pressure, increased serum cholesterol and triglyceride levels, and reduced serum high density lipoprotein cholesterol levels. The correlation between compliance and age was independent of the other risk factors, and the correlation between complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
1
23
2
1
Order By: Relevance
“…Serum glucose or insulin or both have been found to be negatively associated with arterial distensibility in several studies [9, 29±31, 33] but some of these studies did not adequately adjust for blood pressure. One study found no correlation between area under the glucose tolerance curve and arterial distensibility after adjustment for age and blood pressure [34]. There are several possible explanations for conflicting results in these previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Serum glucose or insulin or both have been found to be negatively associated with arterial distensibility in several studies [9, 29±31, 33] but some of these studies did not adequately adjust for blood pressure. One study found no correlation between area under the glucose tolerance curve and arterial distensibility after adjustment for age and blood pressure [34]. There are several possible explanations for conflicting results in these previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Two other studies have yielded discordant results with regard to HDL cholesterol. A positive association, independent of blood pressure, between HDL cholesterol and arterial compliance has been reported in a small group of healthy men (25), whereas an inverse relationship was found in hypertensive men including both normocholesterolemic and hypercholesterolemic subjects (20). Thus, there is no clear evidence for an association between total cholesterol or lipoprotein fractions and PWV.…”
Section: Discussionmentioning
confidence: 97%
“…The Japan Diabetes Complications Study also revealed that, in type 2 diabetic patients, the serum TG, as well as LDL-C, levels were leading predictors of coronary heart disease 44) . For more than two decades, studies have reported a positive relationship between the TG level and atherosclerotic indicators, such as the baPWV [45][46][47] , IMT 48) , forearm blood flow measured with plethysmography 49) , wall thickness measured with echocardiography 50) and flow-mediated dilation (FMD) 51) . In addition, an observational study reported that a decrease in the TG level due to pharmacological therapy was associated with improvement of the baPWV 45) and FMD 51) .…”
Section: Discussionmentioning
confidence: 99%